Efecto de la renta de recursos naturales en la desigualdad de ingresos periodo 1980-2017: nueva evidencia de datos de panel agrupando los países por nivel de ingresos. - Silva Maldonado, Karen Fernanda (2020)
Inequality is an issue of persistent concern in society, especially income inequality which is the difference between the distribution of goods, income and incomes in a country, inequality causes the richer population to become increasingly richer, cruelly affecting the poor population who live with what they need to survive. Therefore, this research aims to: study the impact of natural resource income dependence on income inequality over the period 1980-2017 for countries by income level, using co-integration techniques. The data for this research were taken from the World Bank database (2018), classifying countries by income level. The most relevant results show that there is a long-term balance at the global level and by groups of countries between natural resource income and income inequality. Applying Westerlund's (2007) test, a simultaneous and joint equilibrium was determined in the short term between the variables. Granger's tests determined the existence of one-way causality only in upper-middleincome countries. One policy implication arising from this research is to develop a law on resource exploitation aimed at preventing profits from staying only in mining companies.